JAKET PULLOVER HOODIE DENGAN MOTIF ISTANA SIAK RIAU - Rahmayani Rahmayani; Dini Yanuarmi; Hendratno Hendratno (Institut Seni Indonesia Padangpanjang, 2023)
Siak Palace is a sturdy rectangular building, decorated at the gate with a pair of hawks striking with sharp eyes and consists of two floors. Siak Palace is located in the city of Siak Sri Indrapura, Riau Province. The creation of this work was inspired by the beautiful visual form of the Siak Palace and then created at each end of the pillars of the building. The form of work created is in the form of an L-sized jacket using a written batik technique. The function of this jacket is outerwear that is used to protect from cold weather or fashion. The creation method in this work goes through three stages, namely the exploration stage which is field observation activities, source excavation and data collection. Exploration begins with going to the field to see and observe the shape of the Siak Palace. The design stage is pouring ideas through several alternative sketches, then from several alternative sketches it is determined to be the selected design as a reference in the process of making works. The embodiment stage uses a written batik technique with reactive coloring which is applied to a pullover hoodie jacket. The creation of works uses a theoretical basis of form, function, color, motif, creation and aesthetics. The results of the process of making this work created the Siak Palace motif in the form of five works with the titles